Diagnosis of acute pulmonary embolism. (3rd July 2017) - Righini, M.; Robert‐Ebadi, H.; Le Gal, G.
Summary: Advances in the management of patients with suspected pulmonary embolism (PE) have improved diagnostic accuracy and made management algorithms safer, easier to use, and well standardized. These diagnostic algorithms are mainly based on the assessment of clinical pretest probability, D‐dimer measurement, and imaging tests—predominantly computed tomography pulmonary angiography. These diagnostic algorithms allow safe and cost‐effective diagnosis for most patients with suspected PE. In this review, we summarize signs and symptoms of PE, current existing evidence for PE diagnosis, and focus on the challenge of diagnosing PE in special patient populations, such as pregnant women, or patients with a prior VTE. We also discuss novel imaging tests for PE diagnosis and highlight some of the additional challenges that might require adjustments to current diagnostic strategies, such as the reduced clinical suspicion threshold, resulting in a lower proportion of PE among suspected patients as well as the overdiagnosis of subsegmental PE.